LOCAL GOVERNMENT POLICIES IN IMPROVING ATHLETES' ACHIEVEMENTS - Ekarina Kamanita Br Meliala; Sabaruddin Yunis; Hariadi Hariadi (Indonesia Sport Journal, 2021)
The purpose of this research is to look into how local government initiatives might help Karo athletes improve their performance. The descriptive qualitative data analysis technique was applied in this investigation. Observation and interviews were utilized to obtain data in this study. According to the findings of this study, the Regional Government Policy in Efforts to Improve the Achievement of Karo Athletes is not ideal since various factors such as infrastructure and finance remain. It did not, however, diminish the determination of Karo athletes to attain their goals.Keywords: Policy, Local Government, Achievement